Self-assessment, and not continuous training, improves basic open suturing skills - Vera Hillemans; Otmar Buyne; Ivo de Blaauw; Sanne M.B.I. Botden; Bas H. Verhoeven; Maja Joosten (Medical Education Online)
Background To develop and maintain suturing skills, clinical exposure is important. When clinical exposure cannot be guaranteed, an adequate training schedule for suturing skills is required. This study evaluates the effect of continuous training, ‘reflection before practice’ and self-assessment on basic open suturing skills.Methods Medical students performed four basic suturing tasks on a simulation set up before (‘pre-test’) and after their surgical rotation (‘after-test’). Participants were divided in three groups; the ‘clinical exposure group’ (n = 44) had clinical exposure during their rotation only, the ‘continuous training group’ (n = 16) completed a suturing interval training during their rotation and the ‘self-assessment group’ (n = 16) also completed a suturing interval training, but with the use of reflection before practice and self-assessment. Parameters measured by a tracking system during the suturing tasks and a calculated ‘composite score’ were compared between groups and test-moments.Results A significantly better composite score was found at the after-test compared to the pre-test for all groups for all basic suturing tasks (0.001 ≤ p ≤ 0.049). The self-assessment group scored better at the pre-test than the other two groups for all tasks, except for ‘knot tying by hand’ (0.004 ≤ p ≤ 0.063). However, this group did not score better at the after-test for all tasks, compared to the other two groups. This resulted in a smaller delta of time (‘transcutaneous suture’, p = 0.013), distance (‘Donati suture’ and ‘intracutaneous suture’, 0.005 ≤ p ≤ 0.009) or composite score (all tasks, except for knot tying by hand, 0.007 ≤ p ≤ 0.061) in the self-assessment group.Conclusion Reflection before practice and self-assessment during continuous training of basic open suturing tasks, may improve surgical skills at the start of the learning curve.